Close to death eaudiobook A novel. - Horowitz, Anthony (Hawthorne and Horowitz, 2024)
In New York Times bestselling author Anthony Horowitz's ingenious fifth literary whodunnit in the Hawthorne and Horowitz series, Detective Hawthorne is once again called upon to solve an unsolvable case—a gruesome murder in an idyllic gated community in which suspects abound. Riverside Close is a picture-perfect community. The six exclusive and attractive houses are tucked far away from the noise and grime of city life, allowing the residents to enjoy beautiful gardens, pleasant birdsong, and tranquility from behind the security of a locked gate. It is the perfect idyll, until the Kentworthy family arrives, with their four giant, gas-guzzling cars, gaggle of shrieking children, and plans for a garish swimming pool in the backyard. Obvious outsiders, the Kentworthys do not belong in Riverside Close, and quickly offend every last one of the neighbors. When Giles Kentworthy is found dead on his own doorstep, a crossbow bolt sticking out of his chest, Detective Hawthorne is the only investigator they can call to solve the case. Because how do you solve a murder when everyone is a suspect?